Internal and External Business Environment Analysis of Rabbani Store Tasikmalaya - Putri, Dita Amelia; Arifin, Muhammad; Sintiana, Indah; Nisa, Nabila Mataun; Andrianti, Rini; Al-Fatah, Sopi Nurul (Entrepreneurship Faculty, Universitas Garut, 2024)
This article aims to analyze the internal and external business environment of Rabbani Tasikmalaya. Rabbani is one of the first and largest fashion brand product companies in Indonesia by issuing flagship products in the form of instant headscarves and other Muslim fashion, such as kemko, tunics, kastuns, and other equipment such as ciput/inner and veils. The analysis of the external business environment includes factors such as the political, economic, socio-cultural, and technological environment while the analysis of the internal business environment includes factors such as human resources, financial resources, marketing and sales. The results of the analysis show that Rabbani Tasikmalaya's internal and external business environment is influenced by various factors, such as government regulations, trade policies, market competition, human resource quality, marketing system, and changes in consumer trends. Overall, Rabbani Tasikmalaya internal and external business environment analysis is important to help companies identify opportunities and challenges, as well as formulate appropriate strategies to deal with rapid and complex changes in the business environment.